Review—Zn–Mn Electrodeposition: A Literature Review. Issue 2 (10th January 2020) - Loukil, N.; Feki, M.
Abstract : To improve zinc coating performances in harsh environments, alloying Zn with other metals is an alternative way to generate advanced alloys with better corrosion properties. Zn binary alloys are extensively used in automotive industry for sacrificial corrosion protection of steel. Among Zn alloys, it has been reported that Zn–Mn coatings confer the highest anticorrosive properties, particularly those containing 10%–30% Mn. Zn–Mn alloys can be obtained by electrodeposition, a straightforward and low cost technique. However, Zn–Mn co-deposition poses technical and commercial challenging due to low current efficiency and bath instability. The electrodeposition of Mn-rich deposits from aqueous baths involves significant challenges. The purpose of this paper is to provide a general survey of the research works on Zn–Mn binary alloy electrodeposition. This literature review summarizes the reported data on Zn–Mn co-deposition processes, and the effects of plating conditions with the aim to afford guidelines for the development of more suitable Zn–Mn coatings.